2004
DOI: 10.1255/ejms.633
|View full text |Cite
|
Sign up to set email alerts
|

The Abundances of Fragment Ions Formed via Skeletal Rearrangements from 2,5-Disubstituted-1,3,4-Oxadiazoles and Their Theoretical Calculated Stabilities

Abstract: Protonated molecules of 2,5-di-R1,R2-substituted-1,3,4-oxadiazoles lose isocyanic acid (loss of mass 43) via skeletal rearrangement. This was observed in low-energy CID mass spectra recorded by using electrospray ionisation (ESI). On electron ionisation induced decomposition these compounds also reveal complex skeletal rearrangement, consisting on N2 and CO elimination, leading to the formation of fluorene or indene type ions. It was found that abundances of fragment ions formed in these processes are in good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Our findings based on accurate masses have to be considered a complement of previous papers concerning HNCO loss from protonated 1,3,4-oxadiazoles [8][9][10][11] and the reactions between nitrobenzenes and benzonitrile radical cations [7].…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Our findings based on accurate masses have to be considered a complement of previous papers concerning HNCO loss from protonated 1,3,4-oxadiazoles [8][9][10][11] and the reactions between nitrobenzenes and benzonitrile radical cations [7].…”
Section: Resultsmentioning
confidence: 72%
“…In addition, theoretical calculations performed for various 2,5-diaryl-1,3,4-oxadiazoles have shown that such groups like methoxy or amino (electron-donor groups) at 4 -position favor the protonation of N(3) atom of oxadiazole ring [9,11]. Therefore, formation of N-methoxyphenylbenzonitrilium ion A seems to be favored over the formation of its isomeric ion B (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five‐member heterocyclics containing oxygen and nitrogen atoms reveal interesting mass spectrometric fragmentation pathways 1. Among this class of compounds, 2‐amino‐5‐aryl‐1,3,4‐oxadiazole derivatives are of special interest because they show different biological activities 2–10.…”
Section: Introductionmentioning
confidence: 99%
“…[11] A literature survey showed that few reports are available on mass spectral fragmentation of oxadiazole derivatives. [12][13][14][15][16][17][18][19] As these compounds belong to the category of organic light-emitting diodes (OLEDs) containing an oxadiazole group, the fragmentation behavior of these compounds under mass spectrometric conditions assumes importance and is desirable. These mass spectral studies may help in understanding the degradation process of these materials and in turn their stability and life.…”
mentioning
confidence: 99%